2022
DOI: 10.1002/eat.23792
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure and validity of a diagnostic interview for avoidant/restrictive food intake disorder in a sample of children, adolescents, and young adults

Abstract: Objective There is a paucity of validated diagnostic interviews for avoidant/restrictive food intake disorder (ARFID) to aid identification and classification of cases for both clinical and research purposes. To evaluate the factor structure, construct validity, and criterion validity of the Pica ARFID and Rumination Disorder Interview (PARDI; ARFID module), we administered the PARDI to 129 children and adolescents ages 9–23 years (M = 16.1) with ARFID (n = 84), subclinical ARFID (n = 11), and healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We used the four‐item AEBQ Satiety Responsiveness (AEBQ‐SR) subscale as a measure of low appetite (e.g., “I get full easily”), which has been shown to moderately correlate with an interview measure of lack of interest in eating/food in children, adolescents, and young adults with ARFID (Cooper‐Vince et al, 2022). Items are rated on a 5‐point Likert scale from 1 (“strongly disagree”) to 5 (“strongly agree”) and averaged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the four‐item AEBQ Satiety Responsiveness (AEBQ‐SR) subscale as a measure of low appetite (e.g., “I get full easily”), which has been shown to moderately correlate with an interview measure of lack of interest in eating/food in children, adolescents, and young adults with ARFID (Cooper‐Vince et al, 2022). Items are rated on a 5‐point Likert scale from 1 (“strongly disagree”) to 5 (“strongly agree”) and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…At pre‐ and posttreatment assessment visits, the Pica, ARFID, and Rumination Disorder Interview (PARDI) was administered by an independent, trained evaluator who did not serve as a study therapist. The PARDI is a semi‐structured interview that evaluates ARFID psychopathology (Bryant‐Waugh et al, 2019; Cooper‐Vince et al, 2022). The PARDI severity scale assesses severity of psychosocial impairment, health consequences, and nutritional compromise due to avoidant/restrictive eating.…”
Section: Methodsmentioning
confidence: 99%
“…There are also suggestions of approach-specific outcomes when using CBT-ED with different ARFID presentations [ 62 ], but we are still awaiting the outcome of more definitive studies in the field of CBT-ED for ARFID. However, there is now a set of validated measures to support the evaluation of ARFID and the use of CBT-ED in such cases, rather than relying on other, less relevant eating disorder measures [ 63 , 64 ].…”
Section: New Methodologies In Cbt-edmentioning
confidence: 99%
“…The diagnostic assessment tool was effective, demonstrating moderate inter-rater reliability and signi cantly scoring higher on severity and pro le for individuals with ARFID compared to healthy controls [5]. More recently, research has revealed the strong factor structure and validity of PARDI, indicating that a strong assessment tool for ARFID [9]. Some researchers have indicated that obtaining a diagnosis for ARFID may be in uenced by other neurodevelopmental conditions, like Intellectual and Developmental Disabilities (IDD) [10].…”
Section: Introductionmentioning
confidence: 99%